Keakuratan Hasil Terjemahan Frasa dan Nomina Dari Mesin Penerjemah Atas Artikel Opini Media Massa - La Ode Muhammad Idrus Hamid; Yumna Rasyid; Ratna Dewanti (PRASASTI: Journal of Linguistics, 2024)
This study aims to explore and evaluate the accuracy of phrase and noun translations by machine translators in the context of mass media opinion articles. The research employs a qualitative approach with content analysis. Generally, the qualitative approach involves purposeful sampling, open-ended data collection, text or image analysis, presenting information in the form of visuals and tables, and personal interpretation of the findings. The results of this study reveal several inaccuracies in translations produced by Google Translate, Microsoft Translator, and DeepL Translator. Therefore, further evaluation and precise word choices are necessary to ensure better translation accuracy.